Actions improving HPV vaccination uptake – Results from a national survey in Italy. Issue 21 (15th May 2015) - Giambi, Cristina; Del Manso, Martina; D'Ancona, Fortunato; De Mei, Barbara; Giovannelli, Ilaria; Cattaneo, Chiara; Possenti, Valentina; Declich, Silvia; ,
Highlights: Pre-assign the date for HPV vaccination may improve uptake. Recall non-respondents more than once may improve vaccination uptake. Collaboration among different professional profiles and services is crucial. Multiple interventions are necessary for successful vaccination programmes. Abstract: Background: In Italy, HPV vaccination is offered to 11-year-old girls since 2007. In 2012 coverage was 69%. Strategies for offering and promoting HPV vaccination and coverage rates (26–85%) vary among Regions and Local Health Authorities (LHAs). We conducted a national study to identify strategies to improve HPV vaccination uptake. Methods: In 2011–2012 we invited the 178 LHAs to fill a web-questionnaire, inquiring implementation of HPV vaccination campaigns (immunization practices, logistics of vaccine delivery, training, activities to promote vaccination, barriers, local context). We described type of offer and vaccination promotion in each LHA and studied the association of these factors with vaccination coverage rates. Results: We analyzed 133 questionnaires. The communication tools more frequently used to promote vaccination were: brochures/leaflets (92% of LHAs), fliers/posters (72%). Television (24%) and radio (15%) were less used. Using ≥3 communication channels was associated to a coverage ≥70% (ORadj  = 5.9, 95%CI 2.0–17.4). The probability to reach a coverage ≥70% was higher if the invitation letter indicated a pre-assigned date for HPV vaccination (ORadj  = 7.0, 95%CI 1.2–39.8) and >1 recall for non-respondents was planned (ORadj  = 4.1, 95%CI 1.8–9.3). Immunization services and paediatricians were involved in informative and training activities in most LHAs (80–90%), instead general practitioners, women and family's healthcare services and public gynaecologists in 60–70%, cervical cancer screening services and private gynaecologists in 20–40%. The main factors that negatively affected vaccination uptake were: poor participation to training events of professional profiles different from personnel of immunization services (reported by 58% LHAs), their mistrust towards HPV vaccination (55%) and insufficient resources (56%). Conclusion: The synergy of multiple interventions is necessary for a successful vaccination programme. Practices such as pre-assigning vaccination date and repeatedly recalling non-respondents could improve vaccination uptake. Efforts are required to strengthen the training of different professional profiles and services and encourage their collaboration. Economical resources are needed to promote vaccination.